Controlled unfolding of elastic hinges - Wee, Pin Sheng (Nanyang Technological University, 2022)
Satellite main source of power come from solar panels. Solar panels are thin and intricate therefore it is required to fold and store for safe launching. This means that during the deployment of the solar panels, minimal impact must be ensured to prevent any damages on the solar panels. Thermoplastic, Polycaprolactone were introduced to act as a hinge as they have the damping effect to reduce impact. Vitrimer will also be introduced to compare with Polycaprolactone to see which material is more suitable to be an elastic hinge. Apart from damping characteristic, different properties of both materials will be studied. The main objective is to determine which material can dampen the most impact and which material will be suitable due to their power consumption.